Pemberdayaan Kemitraan Masyarakat Melalui Program Token Pedia dalam Bentuk Pelayanan Kesehatan Jiwa pada Santri Melalui Pengembangan Pesantren Digital di Pesantren Daarus Salam - Alfianto, Ahmad Guntur; Ulfa, Miftakhul; Iriananda, Syahroni; Pramudya, Dian; Ibrohim, Istiyan Maulana Malik; Fitryah, Nahdyatus Nur (Jurnal SOLMA, 2026)
Background: digitalization of Islamic boarding schools and mental health. Token Pedia is an innovation in integrating mental health services and digitalization in Islamic boarding schools. The goal is to facilitate students' access to digital mental health services in Islamic boarding schools through the Token Pedia program. Method: The method comprises 4 steps: socialization, training, technology application, and mentoring/evaluation. The program was implemented for 3 months in 2025 with 10 meetings. Partners of 80 students were located at the Daarus Salam Islamic boarding school. Activities with FGD, interviews, observations, and mental health knowledge questionnaires (MHKQ) with a Cronbach alpha value (0.93) and a paired T-test were carried out. Results: Students' knowledge of health and mental health self-care increased (0.000). 25 students chose to modify their exercise behavior, and students preferred peers (47 students) as a behavior for seeking mental health help. 18 students graduated to become peer counselors. Students were able to apply animated psychoeducational film technology, online games, and mental health applications. Advocacy with the Bantur community health center. Conclusion: Students are provided with digital-based mental health services through the Token Pedia program, resulting in increased knowledge, behavior modification, becoming peer counselors, and the application of mental health technology.